UPAYA GURU PPKn DALAM PENGUATAN KARAKTER DISIPLIN SISWA DI SMPN 3 MATARAM - APRIYANTI, WATUL ARDINA; YULIATIN, YULIATIN; HADI, SAMSUL; KURNIAWANSYAH, EDY (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
Strengthening Character Education (PPK) is crucial in facing the current global changes and developments. The existence of PPK can address various challenges encountered in the education sector. One of the key aspects reinforced in character education is discipline. Therefore, this research aims to identify the steps taken by Civics teachers to strengthen the discipline character of students at SMPN 3 Mataram. The study was conducted at SMPN 3 Mataram using a qualitative approach with a descriptive research type. Data collection was carried out through interviews, observations, and documentation. The results indicate that the efforts made by Civics teachers to enhance the discipline character of students at SMPN 3 Mataram include (a) Teaching Modules: Integrating discipline for independent learning, (b) Introduction: Preparing students with prayers and rules, (c) Learning Models: A structured approach focused on responsibility, (d) Learning Media: Relevant for understanding discipline character, (e) Closing: Delivering moral messages and evaluations, (f) Attitude Assessment: Observations to foster discipline, (g) Teacher Role Models: Teacher discipline serves as an example for students. Factors influencing the efforts of Civics teachers include: (1) Internal Factors: (a) Teacher Competence: A highly competent teacher can serve as a role model for students, (b) Learning Readiness: Teachers must continuously update their knowledge and adapt, (c) Personal Discipline: The teacher's disciplined attitude supports students' discipline character; (2) External Factors: (a) Regular school policies and collaboration are essential for shaping student discipline, (b) The Role of Students: Active participation from students and positive interactions with teachers are key in supporting discipline, (c) School Rules: Student discipline improves through adherence to and enforcement of rules. ABSTRAKPenguatan Pendidikan Karakter (PPK) sangat penting dalam menghadapi perubahan dan perkembangan global saat ini. Keberadaan PPK mampu menjawab berbagai tantangan yang dihadapi dalam dunia pendidikan. Salah satu aspek yang diperkuat dalam pendidikan karakter adalah disiplin. Oleh karena itu, penelitian ini bertujuan untuk mengidentifikasi langkah-langkah yang diambil oleh guru PPKn dalam memperkuat karakter disiplin siswa di SMPN 3 Mataram. Penelitian ini dilaksanakan di SMPN 3 Mataram dengan menggunakan pendekatan kualitatif dan jenis penelitian deskriptif. Pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa upaya yang dilakukan oleh guru PPKn dalam memperkuat karakter disiplin siswa di SMPN 3 Mataram meliputi (a) Modul Ajar: Mengintegrasikan disiplin untuk belajar mandiri, (b) Pendahuluan: Mempersiapkan siswa dengan doa dan aturan, (c) Model Pembelajaran: Pendekatan terstruktur fokus pada tanggung jawab, (d) Media Pembelajaran: Relevan untuk memahami karakter disiplin, (e) Penutup: Menyampaikan pesan moral dan evaluasi, (f) Penilaian Sikap: Observasi untuk membina disiplin, (g) Teladan Guru: Disiplin guru menjadi contoh bagi siswa. Faktor-faktor yang mempengaruhi upaya guru PPKn antara lain: (1) Faktor Internal: (a) Kompetensi Guru: Seorang guru yang memiliki kompetensi tinggi dapat menjadi teladan bagi siswa (b) Kesiapan Belajar: Guru harus terus memperbarui pengetahuan dan beradaptasi (c) Disiplin Pribadi: Sikap disiplin guru mendukung karakter disiplin siswa, (2) Faktor Eksternal: (a) Kebijakan sekolah yang teratur dan kolaborasi penting untuk membentuk disiplin siswa, (b) Peran Peserta Didik: Peran aktif siswa dan interaksi positif dengan guru kunci dalam mendukung disiplin, (c) Aturan Sekolah: Kedisiplinan siswa meningkat lewat kepatuhan dan penegakan aturan.